A DNAzyme‐Based Colorimetric Paper Sensor for Helicobacter pylori. (6th June 2019) - Ali, M. Monsur; Wolfe, Michael; Tram, Kha; Gu, Jimmy; Filipe, Carlos D. M.; Li, Yingfu; Brennan, John D.
Abstract: The reliable detection of pathogenic bacteria in complex biological samples using simple assays or devices remains a major challenge. Herein, we report a simple colorimetric paper device capable of providing specific and sensitive detection of Helicobacter pylori (H. pylori), a pathogen strongly linked to gastric carcinoma, gastric ulcers, and duodenal ulcers, in stool samples. The sensor molecule, an RNA‐cleaving DNAzyme obtained through in vitro selection, is activated by a protein biomarker from H. pylori . The colorimetric paper sensor, designed on the basis of the RNA‐cleaving property of the DNAzyme, is capable of sensitive detection of H. pylori in human stool samples with minimal sample processing and provides results in minutes. It remains fully functional under storage at ambient temperature for at least 130 days. This work lays a foundation for developing DNAzyme‐enabled paper‐based point‐of‐care diagnostic devices for monitoring pathogens in complex samples. Abstract : Ein Lackmustest für Bakterien : Ein selektiver und empfindlicher Papiersensor für den Nachweis von Helicobacter pylori (HP) in menschlichen Stuhlproben wird vorgestellt. Der Sensor erzeugt ein kolorimetrisches Signal in Minutenschnelle und ist mehrere Monate lang stabil, was nicht‐invasive Tests auf HP in abgelegenen Gebieten ermöglicht.